Ceramic powders compaction process / Aidah Jumahat … [et al.] - Jumahat, Aidah; Mahmud, Jamaluddin; M., Sani; M., Azwa (2004)
An experimental work of powder compaction process is done on two type of ceramic powders at room and elevated temperatures. The thermo-mechanical behavior of alumina ceramic powder during cold and warm compaction processes was studied. Experimental works were carried out in the laboratory for a simple cylindrical of compacted powder using a uniaxial die compaction machine. The parameters which were measured were force and displacement. This will provide information on the tooling movement and the required force for compaction of powders. The density is obtained by measuring the dimensions of the green compacted powder and sintered compacted powder. Two types of powder are used i.e pure alumina (NO115) and alumina with acrylic binders (NM9620). The experimental work results were discussed in order to find the reason for such behavior and characteristic. From the compaction results, compactions at 150°C indicate that less force is needed to compact powder compared to compaction at room temperature. Both green and sintered density of compaction temperature at 150°C is higher and relatively close to the theoretical density.